Pengaruh Investasi, Upah Minimum Provinsi (UMP), dan Indeks Pembangunan Manusia (IPM) terhadap Penyerapan Tenaga Kerja di Pulau Jawa Tahun 2010-2020 - Marselino Yuda Pratama; Dewi Rahmi; Ima amaliah (Bandung Conference Series: Economics Studies, 2022)
Abstract. The population density in Indonesia is concentrated on the island of Java. The population on the island of Java is also followed by an increase in the number of the workforce. Efforts to increase labor absorption are certainly inseparable from factors that influence it, such as investment, wages and the Human Development Index (IPM). This study aims to determine the effect of Investment, Human Development Index, and Provincial Minimum Wage (UMP) on employment in Java in 2010-2020. The data in this study are secondary data, namely data from the Central Statistics Agency with a total sample of 6 provinces on the island of Java. The analytical method used is quantitative. This study uses panel data analysis with the Fixed Effect Model (FEM) approach, which was obtained based on the results of the Chow test and Hausman test. The results showed that the investment level and the Human Development Index (IPM) had a significant positive effect on employment in Java, while the Provincial Minimum Wage (UMP) had a negative effect on employment in Java. This shows that efforts to increase labor absorption through various programs and activities as well as increasing community productivity can have an impact on equal employment opportunities. Abstrak. Kepadatan penduduk di Indonesia terkonsentrasi di pulau Jawa. Jumlah penduduk di pulau Jawa juga diikuti dengan peningkatan jumlah angkatan kerja. Upaya peningkatan penyerapan tenaga kerja tentunya tidak terlepas dari faktor-faktor yang mempengaruhinya, seperti investasi, upah dan Indeks Pembangunan Manusia (IPM). Penelitian ini bertujuan untuk mengetahui pengaruh Investasi, Indeks Pembangunan Manusia, dan Upah Minimum Provinsi (UMP) terhadap penyerapan tenaga kerja di Jawa tahun 2010-2020. Data dalam penelitian ini merupakan data sekunder yaitu data dari Badan Pusat Statistik dengan jumlah sampel 6 provinsi di pulau Jawa. Metode analisis yang digunakan adalah kuantitatif. Penelitian ini menggunakan analisis data panel dengan pendekatan Fixed Effect Model (FEM), yang diperoleh berdasarkan hasil uji Chow dan uji Hausman. Hasil penelitian menunjukkan bahwa tingkat investasi dan Indeks Pembangunan Manusia (IPM) berpengaruh positif signifikan terhadap penyerapan tenaga kerja di Jawa, sedangkan Upah Minimum Provinsi (UMP) berpengaruh negatif terhadap penyerapan tenaga kerja di Jawa. Hal ini menunjukkan bahwa upaya peningkatan penyerapan tenaga kerja melalui berbagai program dan kegiatan serta peningkatan produktivitas masyarakat dapat berdampak pada pemerataan kesempatan kerja.